2008
DOI: 10.1016/j.juro.2008.07.022
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect of Coenzyme Q10 and Lipoic Acid on Obstructive Bladder Dysfunction in the Rabbit

Abstract: The current study clearly demonstrates that coenzyme Q10 and alpha-lipoic acid supplementation can improve bladder function after outlet obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Juan et al conducted a study in 2008 with rabbits and reported increased bladder weights after four and seven weeks of BOO. The authors demonstrated that the groups undergoing αlipoic acid and coenzyme Q10 treatment had significantly reduced bladder weights when compared with those of the 7-week obstruction group (16). …”
Section: Discussionmentioning
confidence: 99%
“…Juan et al conducted a study in 2008 with rabbits and reported increased bladder weights after four and seven weeks of BOO. The authors demonstrated that the groups undergoing αlipoic acid and coenzyme Q10 treatment had significantly reduced bladder weights when compared with those of the 7-week obstruction group (16). …”
Section: Discussionmentioning
confidence: 99%
“…Partial outlet obstruction and in vivo models of ischemia have marked deleterious effects on superoxide dismutase and catalase, and as stated above have also been demonstrated to produce significant oxidative damage (10,(12)(13)(14). A variety of antioxidants and natural products that show significant antioxidant properties have been shown to protect the rabbit urinary bladder from contractile, cellular, and subcellular damage and dysfunction mediated by both partial outlet obstruction, and bilateral ischemia / reperfusion (15)(16)(17)(18)(19)(20). One of the most potent of these agents has been shown to be a grape suspension made from whole grapes (13,21,22).…”
Section: Introductionmentioning
confidence: 92%
“…In virtually all of these oxidative stress-linked dysfunctions, antioxidants have proven to be very valuable in their treatment [13,[16][17][18][19]. In addition to specific antioxidants such as coenzyme Q10, alpha lipoic acid and vitamin E, certain natural products have been shown to be effective treatments in regard to these specific diseases [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The urinary bladder is a relatively closed system: that is, I/R can be induced in the bladder with little or no damage to other organ systems [31,32]. Antioxidants have been proven to be very effective in protecting the rabbit bladder from oxidative damage mediated by OBD [16,33].OBD, induces a variety of bladder dysfunctions in addition to I/R including hypertrophy, hyperplasia, apoptosis, and inflammation. In order to eliminate these other effects, we have developed in-vivo and invitro models of bladder I/R [19,34].…”
Section: Introductionmentioning
confidence: 99%